A prospective study of maternal and fetal outcome in repeat LSCS mother - Ganiga, Pradeep; Rudrappa, Shanthala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cesarean section is one of the most commonly performed abdominal operations on women in most countries. The incidence of primary LSCS is increasing all over the world, Consequently, there is a rise in multiple repeat LSCS with associated complications. Previous LSCS is a common indication for repeat LSCS. Primarily, authors aim at studying the influence of repeat LSCS on maternal and fetal outcome in a tertiary centre. Methods: All mothers with one previous LSCS admitted for emergency/elective LSCS at term gestation with singleton pregnancy in A.J. Institute of Medical Sciences and Research centre, Mangalore were recruited in the study from July to December 2018. Detailed history with antenatal risk factors were noted. Intraoperative and postoperative events were noted. Neonatal outcome was also noted correlated. Results: Majority of patients (58%) were in age group of 20-24years. Most of them were between 38 to 39 weeks of gestation. Most common intraoperative complication was bladder adhesion (18% of cases). In postoperative period febrile morbidity (7%) was common followed by urinary tract infection (2%). Most of the neonates (80%) weighed 2.5 to 3kg at birth. The incidence of poor APGAR respiratory distress, NICU admission was not significantly increased. There were 5 morbidly adherent placenta, 1 scar rupture, 4 scar dehiscence, no maternal or perinatal death. Conclusions: Previous caesarean is the most common cause of repeat caesarean and is associated with maternal morbidity. Measures should be taken to reduce primary caesarean sections which indirectly reduces the incidence of repeat cesarean sections.